An estradiol-17β/miRNA-26a/cyp19a1a regulatory feedback loop in the protogynous hermaphroditic fish, Epinephelus coioides. (15th March 2020) - Yu, Qi; Peng, Cheng; Ye, Zhifeng; Tang, Zhujing; Li, Shuisheng; Xiao, Ling; Liu, Su; Yang, Yuqing; Zhao, Mi; Zhang, Yong; Lin, Haoran
Abstract : Cyp19a1a is a key gene responsible for the production of estradiol-17β (E2 ), the main functional estrogen and a major downstream regulator of reproduction in teleost fish. It is widely known that CYP19 gene expression, aromatase activity, and E2 production can influence gonadal differentiation and sex reversal in teleost fish, but the feedback mechanisms whereby E2 regulates cyp19a1a remain poorly understood, especially regarding the potential roles of endogenous small RNA molecules (miRNAs). Here, we identified miR-26a-5p as a regulatory factor of its predicted target gene ( cyp19a1a ). In vitro and in vivo studies showed that miR-26a-5p can decrease cyp19a1a expression. Furthermore, high doses of E2 act as a repressor of miR-26a-5p. This study proposes a regulatory feedback loop whereby E2 regulates cyp19a1a through miR-26a-5p, and suggests that this positive feedback is an important aspect of the control of E2 production. Graphical abstract: Image 1 Highlights: miR-26a-5p is more abundant in the testes than in the ovaries. miR-26a-5p colocalizes with CYP19A1A in theca-interstitial cells of previtellogenesis ovaries and in interstitial cells of testes. miR-26a-5p downregulates cyp19a1a in vitro and in vivo . Estradiol-17β suppresses miR-26a-5p expression in vitro and in vivo .